Dietary choices of New Zealand women during pregnancy and lactation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Albany, New Zealand - Brown, Kimberley Jane (Massey University, 2020)
Background: A woman and her offspring’s health is affected by the maternal diet during pregnancy and lactation. Because of the importance of the diet, there is a large emphasis on women making optimal dietary choices, as recommended by specific guidelines, in pregnancy and lactation. Dietary recommendations are different from other life stages because of altered nutrient requirements and a heightened need for food safety practices. Currently, there is limited evidence available about dietary choices, food safety practices, and sources of nutrition information of New Zealand women during pregnancy and lactation. This information is important to inform strategies to improve the support that women receive during pregnancy and lactation as it identifies what recommendations are currently being effectively communicated. Aim: To investigate New Zealand women’s dietary choices, food safety practices, and sources of nutrition information during pregnancy and lactation. Methods: Women from New Zealand were invited to participate in this observational study between January and June 2019. Participants were required to be pregnant or within six months postpartum. Women completed a demographic, pregnancy food frequency, and food choice questionnaire during or retrospectively to their pregnancy. Postpartum women also completed a lactation food frequency and food choice questionnaire. Results: Women (n=458) consumed a range of foods from the four food groups (fruit and vegetables, breads and cereals, milk and milk products, and meat/meat alternatives/eggs). A large percentage reported adding or increasing, limiting, and avoiding foods. Cow’s milk, the most frequently daily consumed dairy product, was more commonly reported in pregnancy (93%) than lactation (64%). A range of fruit, vegetables, protein, and grain foods were consumed daily in pregnancy and lactation. The majority of women followed food safety recommendations in particular avoidance of alcohol (92%), raw milk products (86%), and raw/smoked/precooked fish/seafood (84%). Dietary information was acquired from a range of sources. The greatest dietary influences included midwives, New Zealand pregnancy and breastfeeding guidelines, and family/friends. Women also frequently reported receiving dietary advice from their lead maternal carer, handouts, the internet, and alternative health practitioners. During lactation, women received information from more potentially unreliable sources including family/ friends, the internet, and alternative health practitioners. Infant symptoms also frequently affected women’s food choices in lactation. Conclusion: Women implement significant dietary changes during pregnancy and lactation. Women are likely to add, remove, and limit food during pregnancy following the New Zealand pregnancy guidelines; advice from health professionals, the internet, magazines/books/newspapers; or because of food safety concerns. Lactating women are likely to make dietary changes because of infant symptoms or advice received from midwives, alternative health practitioners, family/ friends, and the internet.
Keywords: Pregnancy; Nutritional aspects; New Zealand; Lactation; Mothers; Nutrition; Pregnant women; Attitudes; 321004 Nutritional science